(untitled) (Cambridge, 1966)
Progress in Rubber, Plastics and Recycling Technology is a peer-reviewed journal that aims to bridge the gap between research and development and the practical and commercial applications of polymers in a wide range of uses. Current developments and likely future trends are reviewed across key areas of the polymer industry, together with existing and potential opportunities for the innovative use of plastic and rubber products.
Keywords: Cao su,Rubber